2013
DOI: 10.1371/journal.pone.0062865
|View full text |Cite|
|
Sign up to set email alerts
|

Deep Sequencing Reveals Transcriptome Re-Programming of Taxus × media Cells to the Elicitation with Methyl Jasmonate

Abstract: BackgroundPlant cell culture represents an alternative source for producing high-value secondary metabolites including paclitaxel (Taxol®), which is mainly produced in Taxus and has been widely used in cancer chemotherapy. The phytohormone methyl jasmonate (MeJA) can significantly increase the production of paclitaxel, which is induced in plants as a secondary metabolite possibly in defense against herbivores and pathogens. In cell culture, MeJA also elicits the accumulation of paclitaxel; however, the mechani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
61
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(67 citation statements)
references
References 63 publications
(95 reference statements)
5
61
1
Order By: Relevance
“…To date, the most effective strategy for enhancing in vitro taxane production has been considered to be elicitation with methyl jasmonate (MJ), and immense effort has been invested in elucidating its molecular mechanism of action in yew cell suspension cultures, revealing the upregulation of genes engaged in the taxane biosynthetic pathway (Nims et al 2006;Onrubia et al 2010Onrubia et al , 2012Lenka et al 2012;Li et al 2012;Sun et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…To date, the most effective strategy for enhancing in vitro taxane production has been considered to be elicitation with methyl jasmonate (MJ), and immense effort has been invested in elucidating its molecular mechanism of action in yew cell suspension cultures, revealing the upregulation of genes engaged in the taxane biosynthetic pathway (Nims et al 2006;Onrubia et al 2010Onrubia et al , 2012Lenka et al 2012;Li et al 2012;Sun et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Increased secondary metabolite accumulation upon MeJA elicitation is often accompanied with concurrent decreases in culture growth (Kim et al 2005), Thanh et al 2005, Zhang and Turner 2008, Sun et al 2013). MeJA has been shown to broadly induce defense responses and secondary metabolism in plants (Farmer and Ryan 1990, Reymond and Farmer 1998, Seo et al 2001), which diverts carbon resource allocation from primary metabolism (Logemann et al 1995, Pauwels et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…When plants experience various biotic and abiotic stresses, biosynthesis of the secondary metabolites is triggered that helps plants adapt to the challenging environment (Gershenzon and Dudareva, 2007;Hartmann, 2007;Reichling, 2010). Consequently, transcript and metabolite profiling of stress/elicitor-treated plants or cell cultures represents a powerful approach to determine gene function in the biosynthesis of the secondary metabolites (Aerts et al, 1994;Goossens et al, 2003;Suzuki et al, 2005;Zhao et al, 2005;Naoumkina et al, 2008;De Geyter et al, 2012;Lenka et al, 2012;Yu et al, 2012;Ee et al, 2013;Mishra et al, 2013;Sun et al, 2013).…”
mentioning
confidence: 99%
“…Several studies have demonstrated that MeJA treatment can trigger the biosynthesis of all three major classes of secondary metabolites (i.e. terpenoids, phenylpropanoids, and alkaloids) through an extensive transcriptional reprogramming of the plant metabolism (Gundlach et al, 1992;Cheong and Choi, 2003;Zhao et al, 2005;Pauwels et al, 2009;De Geyter et al, 2012;Sun et al, 2013). Here, we carried out transcriptome and selected metabolite analyses to identify the MeJA-responsive secondary metabolic pathways of sweet basil (Ocimum basilicum), which is a plant of the Lamiaceae family with highly valued aromatic and medicinal properties.…”
mentioning
confidence: 99%